Operando evidence of Cu+ stabilization via a single-atom modifier for CO2 electroreduction. Issue 48 (7th December 2020) - Zhang, Wei; He, Peng; Wang, Chao; Ding, Tao; Chen, Tao; Liu, Xiaokang; Cao, Linlin; Huang, Tianming; Shen, Xinyi; Usoltsev, Oleg A.; Bugaev, Aram L.; Lin, Yue; et al.
Abstract : Single-atom Sn modified Cu2 O nanosheets with stable intermediate Cu + species for efficient CO2 -to-CO conversion proved by operando XAFS. Abstract : Oxide-derived Cu materials are most commonly used as electrocatalysts for the carbon dioxide reduction reaction (CO2 RR). Previous studies have proved that Cu + and residual subsurface oxygen species can enhance the CO2 RR activity; however the stable presence of Cu + remains a subject of debate. Here, we design a strategy of single-atom Sn anchored on Cu2 O nanosheets to stabilize the key Cu + species for electroreduction of CO2 . Operando synchrotron X-ray absorption spectroscopy and statistics analysis distinguish the active Cu + and reduced Cu + species, and reveal that the constructed Sn–O–Cu sites with charge transfer can significantly enhance the resistance of copper oxides to reduction. Operando infrared spectroscopy suggests that the survival of Cu + species on the catalyst surface promotes the adsorption of *CO during the CO2 RR, leading to the obvious improvement of CO2 -to-CO conversion. Our results demonstrate the role of a single-atom-modifier in both stabilizing Cu + species and enhancing the CO2 RR selectivity of oxide-derived Cu catalysts.